Distance Education Use in Rural Schools - Wallace H. Hannum; Mathew J. Irvin; Jonathan B. Banks; Thomas W. Farmer (Journal of Research in Rural Education, 2009)
A national survey of rural school systems in the United States was conducted to determine the extent to which distance education is being utilized by rural schools, the technologies used, the curriculum areas impacted, the perceived needs for distance education, their satisfaction with distance education, and the barriers to distance education use. Data were collected through telephone surveys with 394 school districts selected at random. Most rural school districts were currently using distance education. The subjects most often offered by distance education were math, foreign language, and English. A large majority of the districts indicated satisfaction with distance education courses; almost half stated they were very satisfied. The majority of students who enrolled in distance education courses completed these courses. Two-thirds of the districts indicated a need for additional distance education courses. Only a small portion of school districts indicated they are able to offer all the advanced and enrichment classes that students need without using distance education. The large majority of the districts did not see connectivity as a barrier to distance education use. Common barriers were funding, scheduling, and difficulty implementing distance education courses. The two most common formats for distance education courses in rural schools were two-way videoconferencing courses and online courses. Implications for future research are discussed.